DESAIN FOTOTRANSFOMATOR PLAT TEMBAGA (II) OKSIDA CuO PADA ASAM HUMAT - Yuni Aulia Putri Djasli; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2019)
This study was conducted using a phototransformator reactor which was used to degrade humic acid with calcined photocatalyst of CuO plate for 1 hour at 4000C. This reactor was designed in hexagonal form made of glass with a thickness of 3 mm, in this reactor filled with 200 mL of humic acid with the help of sunlight. The phototransfomator process is carried out through a process of degradation of humic acid using a reactor which is performed at 1, 2, 3, 4, 5 hours. Absorption of visible light humic acid before and after degradation is 265 nm. The results show that in the outer light the highest value occurs at 2 hours which is 49.70% Keyword : photocatalyst, photransformator, plate CuO, degradation, %Degradation (%D), humic acid